Extracorporeal Membrane Oxygenation in a Pediatric Patient with Hepatopulmonary Syndrome and Interrupted Inferior Vena Cava After Living Related Liver Donation. Issue 3 (March 2019) - Phillips, Michael R.; Priest, Marc; Beaty, Christopher; Parker, Robert; Meyer, Marisa; Dunn, Stephen; Froehlich, Curtis D.; Dirnberger, Daniel R.; Martin, Abigail E.; Ogino, Mark T.
Abstract : Extracorporeal membrane oxygenation (ECMO) is used for cardiopulmonary dysfunction. Hepatopulmonary syndrome (HPS) occurs in the setting of liver failure and may cause hypoxemia. Previous reports have described the use of ECMO for HPS after liver transplant. Our patient is a 19-month-old female with biliary atresia, an interrupted inferior vena cava, and HPS on 8 liters per minute of high-flow oxygen. Following liver transplantation, her postoperative course was complicated by severe hypoxemia requiring ECMO. Due to her interrupted inferior vena cava, our standard bi-caval cannula could not be used. Hence, a 16-French double lumen venovenous right internal jugular to right atrial cannula was used to provide extracorporeal life support. She was decannulated after 17 days, remained intubated for 2 days, and weaned to room air over the next 3 weeks. This is the third pediatric liver transplant patient supported with ECMO identified in the literature, and the youngest and smallest of those reported. This approach to cannulation is unique because of the use of a double lumen venovenous cannula for HPS in a child, selected due to complex anatomy. Posttransplant ECMO may provide pediatric patients with HPS and posttransplant hypoxemia a period of support for their pulmonary remodeling and recovery from HPS.